The service quality evaluation on tourist loyalty in Malaysian hotels by the mediating role of tourist satisfaction - Keshavarz, Yousef; Ali, Mass Hareeza (Richtmann Publishing, 2015)
The purpose of this study is to investigate the influence of service quality on tourism loyalty in the hotel industry. Data were collected from international tourists at several top interested places locations in Kuala Lumpur. The study sample included international tourists who stay in four and five star hotels in Kuala Lumpur. Service quality with five dimensions includes reliability, assurance, responsiveness, tangible, and empathy is considered as independent variables. From the result of the study, it was found that service quality affects tourist satisfaction and loyalty directly. The finding of this study is helpful for hotel industry. In fact, the finding of this research informs hotelier to understand about the tourist attitude toward service quality in hotel and its impact on their satisfaction and loyalty.